THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON THE COMMITMENT OF BANDA ACEH STATE SENIOR HIGH SCHOOL TEACHERS - Akmaluddin Akmaluddin; Basri Basri; Mardhatillah Mardhatillah (Teunuleh Publisher, 2021)
This study aims to determine: (1) the influence of leadership on motivation, (2) the influence of leadership on teacher commitment, (3) the effect of motivation on teacher commitment. Influence The study population was all public high school teachers in Banda Aceh City with a total sample of 252 people taken by proportional random sampling, and the data were analyzed using path analysis after calculating the correlation of all research variables in the form of a matrix. The research findings show that the commitment of public high school teachers in Banda Aceh City is directly influenced by the principal's leadership and teacher work motivation. Based on hypothesis testing, it can be concluded: (1) there is a direct influence of leadership on teacher commitment, (2) there is a direct influence of principal's leadership on teacher commitment, (3) there is a direct influence of work motivation on teacher commitment. Suggestions that can be concluded in this study are: (1) the provincial government of Aceh is authorized to produce policies in accordance with the findings in this study (2) for the head of the Aceh education office to improve the quality of policy professionalism directed at the quality of school principals and teacher commitment (3) for school principals to be able to take into account in forming teacher organizational commitment to their schools (4) for teachers to be able to make reference in carrying out their duties as teachers.